Fisioterapia como tratamiento coadyuvante de la cefalea tensional - Román Olivo, Andrea Dayana (2022)
ABSTRACT Tension headache is one of the pathologies with a prevalence between 30 and 78% worldwide causing consequences even at a socioeconomic level, generally patients have symptoms such as: headache of oppressive characteristic, sensitivity in scalp, neck and shoulder muscles. Tension headache is caused when the muscles of the neck and scalp tense or contract as a response to stress, depression, anxiety or head trauma. The research focused on the modality of bibliographic review, to know the benefits of physiotherapy as an adjuvant treatment in tension headache, determining the contribution provided by the application of different techniques and physical agents for the treatment of tension headache, seeking to improve the quality of life of patients who present this pathology, whether chronic or acute. The research work included 42 scientific articles which were selected from databases: PEDro, PubMed, Science Direct, SciELO, RIECS, Cochrane Database and BvSalud, complying with the proposed inclusion and exclusion criteria. According to the authors of the works reviewed, physiotherapy manages to improve the clinical condition by providing wellbeing to the patient, achieving positive effects in terms of the intensity, frequency and duration of pain, disability, impact, quality of life and range of motion at the cranio-cervical level in patients with tension headache. Among the most commonly used techniques are manual therapy, suboccipital inhibition, relaxing massage, cervical manipulation, pressure maintained on trigger points and cervical mobilization, no superiority was found between one technique with respect to another. Key words: tension headache, physiotherapy, trigger points, manual therapy, disability.